Training Of Trainers (ToT) for Peer Counselors to Enhance Emotional Regulation and Self-Efficacy - Widyadhari, Sahila Aurellia; Nurwianti, Fivi (Kuras Institute, 2025)
Adolescent mental health is a growing concern, with increasing cases of mental disorders among teenagers. Peer counseling has proven effective in emotional support, highlighting the need for well-trained peer counselor trainers. This study evaluates the effectiveness of a Training of Trainers (ToT) program in enhancing future peer counselor trainers' self-efficacy and emotional regulation skills. The two-day training consisted of five interactive sessions covering peer counseling theory, active listening techniques, emotional regulation strategies, and practical counseling exercises. A total of 10 psychology students from Universitas Indonesia participated. Evaluation using the General Self-Efficacy Scale (GSES) and Emotion Regulation Questionnaire (ERQ) showed a significant increase in self-efficacy, cognitive reappraisal strategies, and a reduction in expressive suppression. Qualitative analysis also indicated that participants felt more confident and better managed emotions in group dynamics. These findings suggest that the ToT program effectively equips future peer counselor trainers. Further research is recommended to expand the program’s implementation and assess its long-term impact in school settings